Lesotho : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Lesotho assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Lesotho perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Lesotho on: 1) their views regarding the general environment in Lesotho; 2) their overall attitudes toward the WBG in Lesotho; 3) overall impressions of the WBGs effectiveness and results, knowledge work and activities, and communication and information sharing in Lesotho; and 4) their perceptions of the WBGs future role in Lesotho.